LOCAL GOVERNMENT CAPACITY IN THE AFTERMATH: ISIS AS A MEDIATOR BETWEEN AUDITOR NARCISSISM AND OPINION SHOPPING IN IRAQI LISTED COMPANIES (Lex localis - Journal of Local Self-Government, 2025)
The present study aims to assess the relationship between auditor narcissism and audit opinion shopping in listed firms on the Iraq Stock Exchange. Moreover, it is willing to capture the mediatory role of the Islamic State of Iraq and Syria (ISIS) on the relationship between auditor narcissism and audit opinion shopping. The multivariate regression model is used for hypothesis testing for this study. Research hypotheses were also examined using the listed firms on the Iraq Stock Exchange using the synthetic data technique-based multivariate regression pattern. The obtained results show that there is a positive and significant relationship between auditor narcissism and audit opinion shopping, which means that an increase in auditor narcissism leads to increased audit opinion shopping. Moreover, hypothesis testing results show that the presence of ISIS strengthens the relationship between auditor narcissism and audit opinion shopping. Since the present study is carried out in an emergent country like Iraq, its effects on the country's economy can contribute to developing science and knowledge and fill the existing gap in the topical literature.